AIE-induced fluorescent vesicles containing amphiphilic binding pockets and the FRET triggered by host–guest chemistry1. Issue 50 (25th June 2015) - Zhang, Meng; Yin, Xianpeng; Tian, Tian; Liang, Yun; Li, Weina; Lan, Yue; Li, Jian; Zhou, Meimei; Ju, Yong; Li, Guangtao
<x xml:space="preserve">Abstract</x> Synergetic combination of TPE and bile acid units could directly afford uniform fluorescent vesicles with amphiphilic binding sites.